Pemberdayaan Ibu Rumah Tangga: Pelatihan Minyak Jelantah Jadi Sabun Ramah Lingkungan - Fernando, Agus; Hakim, Dani Lukman; Hamzah, Dadang Amir (Jurnal Pemberdayaan Umat, 2024)
Purpose: The management of used cooking oil waste poses a significant environmental challenge, as it is often not properly managed, resulting in negative impacts on human health and the environment. This training aimed to increase housewives’ knowledge about the dangers of used cooking oil waste, provide skills in making soap as an eco-friendly solution, and support family economies. Research methodology: This activity involved three stages: preparation, implementation, and monitoring evaluation. During the implementation stage, participants received materials on the impact of used cooking oil, a demonstration of soap-making, training in basic bookkeeping, and marketing techniques. Results: The evaluation results showed that 86.7% of the participants intended to apply training at home. The activity had a positive impact by raising environmental awareness and opening new business opportunities for participants. Limitations: This community service is limited to the scope of RW 016, Simpangan Village, and involves only 14 participants; therefore, generalizing the results to a broader community requires further evaluation. Contribution: This research is useful in the fields of community empowerment, environmentally-based waste management, and social entrepreneurship, particularly in densely populated areas with middle-to-low economic levels.